Microscopic Simulation of Coordinated Route in the City of Zilina - Alica Kalasova; Lubomir Cernicky; Simona Kubikova (Communications - Scientific letters of the University of Zilina, 2014)
Urban agglomerations are characterized by concentrating a large number of vehicles in a confined space, while it is not possible to increase the range of the road communications. Therefore, it is necessary to achieve better and more efficient use of existing communications. Creation of successful city management means to integrate and optimize the quality of transport. When intersection signal control is used, not only the high degree of safety is ensured, but also permeability of the intersection increases. For better and more effective use of intersections we use a management in real time. We model the program of management by microscopic simulation. In our paper we use simulation of coordination at intersections in the city of Zilina. As modeling tools we use software Aimsun and MATSim which allow microscopic simulation. Finally, in our paper we compare both of the software tools.